Differentiated Instruction in Medical Laboratory Science Education in Eswatini: Challenges and Successes - Phumuzani Mpofu; Mlungisi Patrick Msibi; Mkhumbulo Ndlovu (Studies in Learning and Teaching, 2026)
Differentiated Instruction (DI) is a learner-centred approach that adapts content, processes, assessments, and learning environments to address students’ diverse needs. Although widely used in general education, its application in laboratory-based medical sciences remains limited, especially in resource-constrained tertiary contexts. This qualitative study examined the challenges and successes of DI in Medical Laboratory Sciences (MLS) classrooms across three higher education institutions in Eswatini. Guided by Cultural-Historical Activity Theory and a transformative paradigm, semi-structured interviews were conducted with 20 purposively selected lecturers. Thematic analysis of the interview data indicated that participants perceived differentiated instruction (DI) as an adaptive and inclusive strategy that supports student engagement, conceptual understanding, and practical competence. Participants described practices such as tiered tasks, case-based learning, peer support, flexible grouping, multimodal resources, and varied assessment methods as ways through which DI could be implemented in the classroom. However, large class sizes, limited laboratory resources, time constraints, inadequate training, and rigid institutional structures constrained implementation. Despite these barriers, DI improved weaker students’ confidence, engagement, and laboratory accuracy while fostering collaboration. Participants advocated for institutional support, resource enhancement, and DI-focused professional development. The findings suggest that differentiated instruction may offer a practical pedagogical approach for supporting inclusive and competency-based learning in medical laboratory sciences programmes within resource-constrained tertiary institutions in Eswatini, while also contributing empirical insight into how DI is perceived and applied in specialised health science classrooms.